Clinical pathway for early discharge after complete primary repair of exstrophy and epispadias by using a spica cast. Issue 4 (August 2015) - Sack, Bryan S.; Kryger, John V.; Mitchell, Michael E.; Durkee, Charles T.; Lyon, Roger; Groth, Travis W.
Summary: Introduction/Objective: Secure closure of the pubic diastasis during bladder exstrophy and epispadias repair decreases the abdominal wall tension at the time of reconstruction. Pelvic osteotomies are routinely performed at the time of abdominal wall and bladder reconstruction in order to more easily facilitate pubic symphyseal diastasis approximation. Postoperative pelvic immobilization is performed by methods that include modified Buck's traction, modified Bryant's traction, and spica casting. People undergoing closure often require inpatient hospitalization for 2–8 weeks because of the pelvic immobilization. The present study examined the findings from a clinical pathway for early discharge after complete primary repair of exstrophy (CPRE) and proximal epispadias repair with spica casting. Methods: The present study is a retrospective review of patients that underwent pelvic osteotomies with spica casting at the time of CPRE or proximal epispadias repair from November 2006 to March 2013. All patients had anterior innominate osteotomies and spica cast pelvic immobilization. Results: Pelvic osteotomies and spica cast pelvic immobilization were performed on 17 children. The median postoperative stay was 6.0 days and the subdivided results are in Table. No children experienced an abdominal or orthopedic complication. A few children required minor cast adjustments to relieve pressure. After cast removal, no skin breakdown, pressure necrosis, or nerve palsy were found. The median length of casting without pinning was 31 (26–48) days. Table Length of hospital stay Total Male/Female Median age at surgery (days) Median postoperative stay (days) Primary bladder exstrophy 11 5/6 4.0 (1–125) 6.5 (3–15) a Bladder exstrophy revision 4 2/2 404 (79–1764) 5.5 (5–8) Epispadias 2 1/1 134 (71–197) 5.0 (4–6) Total 17 8/9 15.0 (1–1764) 6.0 (3–15) a Exclusion of one patient with prolonged hospital course secondary to seizure disorder. Discussion: The use of spica cast pelvic immobilization after exstrophy and epispadias repair is safe and allows for earlier discharge when compared to other methods of pelvic immobilization. However, although the family appreciates early discharge and additional bonding, the priority is the success of the closure. The present findings demonstrate, and are corroborated by other spica cast publications, that spica casting is as effective as modified Bryant's traction or modified Buck's traction. The success rates for CPRE with spica casting are similar to published staged repairs and have the benefit of allowing for bladder cycling, which potentially enables better bladder growth and development. If success and complication rates are comparable amongst the different pelvic immobilization groups, then variables including hospital length of stay and cost become appropriate comparisons. Conclusion: The shortened discharge time, along with a significant decrease in acuity of care leads to significant decreases in hospital costs. Additional hospital stay when using modified Bryant's traction or modified Buck's traction with external fixation will accrue significant hospital costs.